Proteomic investigation of interhyphal interactions between strains of Agaricus bisporus. Issue 6 (June 2020) - O'Connor, Eoin; Owens, Rebecca A.; Doyle, Sean; Amini, Aniça; Grogan, Helen; Fitzpatrick, David A.
Abstract: Hyphae of filamentous fungi undergo polar extension, bifurcation and hyphal fusion to form reticulating networks of mycelia. Hyphal fusion or anastomosis, a ubiquitous process among filamentous fungi, is a vital strategy for how fungi expand over their substrate and interact with or recognise self- and non-self hyphae of neighbouring mycelia in their environment. Morphological and genetic characterisation of anastomosis has been studied in many model fungal species, but little is known of the direct proteomic response of two interacting fungal isolates. Agaricus bisporus, the most widely cultivated edible mushroom crop worldwide, was used as an in vitro model to profile the proteomes of interacting cultures. The globally cultivated strain (A15) was paired with two distinct strains; a commercial hybrid strain and a wild isolate strain. Each co-culture presented a different interaction ranging from complete vegetative compatibility (self), lack of interactions, and antagonistic interactions. These incompatible strains are the focus of research into disease-resistance in commercial crops as the spread of intracellular pathogens, namely mycoviruses, is limited by the lack of interhyphal anastomosis. Unique proteomic responses were detected between all co-cultures. An array of cell wall modifying enzymes, plus fungal growth and morphogenesis proteins were found in significantly ( P  < 0.05) altered abundances. Nitrogen metabolism dominated in the intracellular proteome, with evidence of nitrogen starvation between competing, non-compatible cultures. Changes in key enzymes of A. bisporus morphogenesis were observed, particularly via increased abundance of glucanosyltransferase in competing interactions and certain chitinases in vegetative compatible interactions only. Carbohydrate-active enzyme arsenals are expanded in antagonistic interactions in A. bisporus . Pathways involved in carbohydrate metabolism and genetic information processing were higher in interacting cultures, most notably during self-recognition. New insights into the differential response of interacting strains of A. bisporus will enhance our understanding of potential barriers to viral transmission through vegetative incompatibility. Our results suggest that a differential proteomic response occurs between A. bisporus at strain-level and findings from this work may guide future proteomic investigation of fungal anastomosis. Highlights: Unique proteomic responses detected between all Agaricus bisporus strain co-cultures. Cell wall, fungal growth and morphogenesis proteins are differentially abundant. Nitrogen starvation evident between competing and non-compatible strains. Carbohydrate-active enzymes are expanded in antagonistic A. bisporus interactions.